2011
DOI: 10.1371/journal.pone.0019201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Retention in Care after Starting Antiretroviral Therapy in a Rural South African Programme

Abstract: IntroductionThe prognosis of patients with HIV in Africa has improved with the widespread use of antiretroviral therapy (ART) but these successes are threatened by low rates of long-term retention in care. There are limited data on predictors of retention in care, particularly from rural sites.MethodsProspective cohort analysis of outcome measures in adults from a rural HIV care programme in Madwaleni, Eastern Cape, South Africa. The ART programme operates from Madwaleni hospital and seven primary care feeder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
64
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 31 publications
(31 reference statements)
12
64
1
1
Order By: Relevance
“…(A recent study from the Eastern Cape showed that retention in care was reduced if pregnant women were started on ART as inpatients, 9 perhaps because pregnant women view ART as primarily to protect their babies). Is HAI, as a cause of death in HIV-infected patients, peculiar to tertiary hospital inpatients or does it apply to all HIV-infected hospitalised patients?…”
Section: Fig 1 Main Primary Diagnoses and Co-morbid Illnesses In Himentioning
confidence: 99%
“…(A recent study from the Eastern Cape showed that retention in care was reduced if pregnant women were started on ART as inpatients, 9 perhaps because pregnant women view ART as primarily to protect their babies). Is HAI, as a cause of death in HIV-infected patients, peculiar to tertiary hospital inpatients or does it apply to all HIV-infected hospitalised patients?…”
Section: Fig 1 Main Primary Diagnoses and Co-morbid Illnesses In Himentioning
confidence: 99%
“…[5,6] It has previously been suggested that decreased time before initiation of treatment, resulting in a decreased number of preparation sessions might in part account for this finding. [5] Time from diagnosis to initiation of ART was not examined in the current study. There may be links between illness awareness, insight into risk of infection, insight into need for treatment and subsequent adherence to treatment.…”
Section: Discussionmentioning
confidence: 96%
“…[3,4] Research has also shown that medical patients initiated on ART as inpatients have poorer outcomes than those initiated as outpatients. [5,6] Negative perceptions with regard to rates of adherence, future clinic attendance and long-term outcome may affect the decision to initiate ART in HIV-positive psychiatric patients, especially in patients requiring hospitalisation, in effect depriving these patients of potentially lifesaving treatment. [7] With this in mind, the Luthando Neuropsychiatric HIV Clinic (Luthando Clinic) at Chris Hani Baragwanath Academic Hospital (CHBAH), Soweto, was established, providing specialised integrated treatment for HIV-positive psychiatric patients at a tertiary academic level.…”
Section: Articlementioning
confidence: 99%
“…Nonetheless, treatment scale-up in South Africa has succeeded in vastly increasing the numbers of people benefitting from ART. As the service evolves and expands, an additional challenge revolves around how best to retain patients over time 4 5…”
mentioning
confidence: 99%